2014
DOI: 10.17969/agripet.v14i2.1886
|View full text |Cite
|
Sign up to set email alerts
|

Kecernaan Bahan Kering dan Bahan Organik dan Degradabilitas Serat pada Pakan yang Disuplementasi Tanin dan Saponin

Abstract: The study was conducted to assess the effect of the addition of tannins, saponin and their combinations on the feed, as defaunation agent in the dry matter and organic matter digestibility and ADF, NDF degradability. The study used an experimental method with a completely randomized design. The treatments were T0 : feed without supplementation; T1: feed supplementation with 1,2% saponin; T2 : feed with supplemetation combined of 0,5% tannin and 0,9% saponin; T3 : feed with supplementation combined of 1,0% tann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 5 publications
0
11
0
8
Order By: Relevance
“…Bahan organik merupakan bagian dari bahan kering kecuali abu, sehingga apabila bahan kering meningkat akan mengakibatkan terjadinya peningkatan kandungan bahan organik pada bahan atau sebaliknya (Wahyuni et al, 2014). Kecernaan bahan organik adalah banyaknya nutrien yang terkandung dalam suatu bahan pakan seperti karbohidrat, protein, lemak dan vitamin yang dapat dicerna oleh tubuh ternak.…”
Section: Pendahuluanunclassified
“…Bahan organik merupakan bagian dari bahan kering kecuali abu, sehingga apabila bahan kering meningkat akan mengakibatkan terjadinya peningkatan kandungan bahan organik pada bahan atau sebaliknya (Wahyuni et al, 2014). Kecernaan bahan organik adalah banyaknya nutrien yang terkandung dalam suatu bahan pakan seperti karbohidrat, protein, lemak dan vitamin yang dapat dicerna oleh tubuh ternak.…”
Section: Pendahuluanunclassified
“…This result was lower compared with research done by Isah et al (2012) reported that organic matter in vitro digestibility was 45.86%. Wahyuni et al (2014) stated that the in vitro digestibility of forages is influenced by the fiber components consisting of cellulose and lignin. In addition, the crude fiber and lignin components also have the ability to inhibit fermentation in vitro, so that the higher the crude fiber contents, the lower in vitro digestibility.…”
Section: In Vitro Digestibilitymentioning
confidence: 99%
“…Konsentrasi VFA parsial dipengaruhi oleh komposisi nutrien bahan pakan. Konsentrasi asam asetat, propionat dan butirat hasil dari fermentasi bahan pakanyang menggambarkan tingkat kelarutan karbohidrat dan protein selama proses fermentasi (Wahyuni et al, 2014).…”
Section: Konsentrasi Asetat Propionat Dan Butiratunclassified